CO2 storage potential of the Qiongdongnan Basin, northwestern South China Sea. Issue 6 (21st May 2014) - Zhang, Cuimei; Zhou, Di; Li, Pengchun; Li, Fucheng; Zhang, Yunfan; Sun, Zhen; Zhao, Zhongxian
Abstract The Qiongdongnan Basin, located off Hainan Island, South China, is a petroliferous basin containing what is currently the largest offshore‐producing gas field in China (YA13–1). This paper evaluated the potential of CO2 storage in the Qiongdongnan Basin to provide background data on CO2 storage capacities for regional planning purposes. Four regional seals and high‐quality reservoirs exists in the basin, in mostly marine sequences. The estimated mean effective CO2 storage capacity of the basin is 41 GtCO2, determined from published data and the Carbon Sequestration Leadership Forum methodology for assessing oil and gas storage capacity; the majority of the storage capacity is in saline formations and oil and gas field (15 MtCO2 and 832 MtCO2, respectively). The prospective areas for CO2 storage in the Qiongdongnan Basin are in the belts of the Northern Depression and the Central Uplift. The Yacheng Uplift, as the most favorable area for CO2 storage, contains the YA13–1 gas field, which has an estimated mean effective CO2 storage capacity of 73 MtCO2. The Qiongdongnan Basin may provide storage sites for CO2 stripped from the CO2‐enriched gas from the basin itself, or from the emission sources in Hong Kong and Guangdong Province. However, industrial development on Hainan Island is weak, as the island was defined as an 'island for international tourism' by the Chinese government in 2009. The feasibility of transporting CO2 to storage sites in the Qiongdongnan Basin using the pipeline now transporting gas from the YA13–1 gas field to Hong Kong should be explored.